Grief and Posttraumatic Growth Among Chinese Bereaved Parents Who Lost Their Only Child: The Moderating Role of Interpersonal Loss - Xu, Xin; Wen, Jun; Zhou, Ningning; Shi, Guangyuan; Tang, Renzhihui; Wang, Jianping; Skritskaya, Natalia A. (Frontiers in Psychology, 2020)
Objective: Losing the only child is considered as the most severe kind of bereavement. It can trigger intense grief symptoms along with loss of psychosocial resources, but meanwhile, it can also lead to posttraumatic growth (PTG). The current study aimed to examine (a) whether a curvilinear relationship exists between grief and PTG, and (b) the moderating role of resources-loss among Chinese bereaved parents who lost their only child (shidu parents). Methods: 199 shidu parents from five provinces completed the assessment packet covering prolonged grief symptoms and PTG, as well as resource loss. Hierarchical regression analyses were computed to examine the curvilinear relationship and the moderating effect of interpersonal loss and socio-economic loss. Results: There was no significant curvilinear relationship between grief and PTG in shidu parents. Under the high levels of interpersonal loss, shidu parents’ PTG scores decreased as the severity of grief increased. However, the socio-economic loss did not show a significant moderating effect. Conclusion: The results of the current study did not show a significant curvilinear relationship between grief and PTG in shidu parents. High levels of grief coupled with high levels of interpersonal loss may interfere with their ability to achieve PTG. Therefore, evaluating degrees of interpersonal loss seems to be an important part of the treatment process when working with shidu parents. To facilitate their adaptation from a positive perspective, helping them maintain existing or develop new interpersonal relationships may be helpful.